Parental problem drinking and adolescent externalizing behaviors: The mediating role of family functioning. (12th June 2015) - Finan, Laura J.; Schulz, Jessica; Gordon, Mellissa S.; Ohannessian, Christine McCauley
ABSTRACT: This study explored relationships among parental problem drinking, family functioning, and adolescent externalizing behaviors. The unique effects of maternal and paternal drinking were examined separately for girls and boys. The sample included 14–19 year old U.S. adolescents ( M age = 16.15; SD = .75; 52.5% female) and their parents. Participants completed surveys in the spring of 2007 and 2008. Structural equation modeling was used to conduct path analysis models. Results showed the distinctive and adverse effects of parental problem drinking on adolescent alcohol use, drug use, rule breaking, and aggressive behavior over time. Findings also highlighted the indirect and mediating roles of family functioning. For both girls and boys, family cohesion mediated the relationship between parental problem drinking and adolescent externalizing behaviors. For girls, adolescent–father communication predicted increased externalizing behaviors over time. These findings draw attention to the importance of exploring adolescent and parent gender when examining parental problem drinking, family functioning, and externalizing behaviors.